Desenvolvendo as capacidades dinâmicas em startup do setor de tecnologia da informação - Löw, Viviane Freire (Universidade do Vale do Rio dos Sinos, 2011)
This study aims, through a case study, identify which and how are developed the dynamic capabilities, in an environment of technology and innovation, and what factors contribute to their creation and development. The main topic was Dynamic Capabilities (CDs), and the Resource Based View (RBV) as an important complement to the discussions. The company target of this study, E-Projeti Tecnologia, a startup in the IT sector and installed in one of the leading technology parks in Brazil, Tecnosinos. To this end, the case study, related to the internal environment of the company, identified the existence of dynamic capabilities, such as (1) ability to anticipate customer needs and (2) product innovation, service and marketing. Moreover, with the main results of this study was constructed a map of dynamic capabilities which presented the elements responsible for the creation and development of such capabilities. The items were presented under the headings: "resources, processes, position and trajectory." The first category is related to VBR and the elements identified were: (a) human resources, technical expertise, business intelligence and strategic focus, (b) physical resources, infrastructure and location, (c) organizational resources, networking. The other three categories are related to the CDs in category "processes," three subcategories were identified, people, products and operations. The processes identified were (a) people: attracting and retaining talent and career development plan, (b) products: development of the product mix, (c) operations: development of sales strategy and strategy development services. In the category "position" were identified some differences in technology, as tools GwBox and Kaseya, and the last category "path" they highlight was the formal and informal structure of the company, (a) as a formal structure it was pointed the Company Management, defined from its organization chart, where areas and responsibilities were mapped and according to individual skills and business needs; (b) stood out as informal the replication of knowledge and informal leadership. It was evident that the development of dynamic capabilities is the result of coordination and mobilization of resources and capabilities of the company and also the ability to adapt and the ability to change skills which help an enterprise to work its strategy in a dynamic way. It was also evident that despite being a young company, managing the business is being conducted in an organized manner, taking into account the best practices outlined in the market and in the literature on organizational strategies. Allied to this, the fact that the company is in an environment of technology, such as Tecnosinos, drives to seek more excellence to its products and services with quality and innovation as north.
Keywords: Capacidades dinâmicas; Recursos; Competências; Processos; Inovação; Dynamic capabilities; Resources; Competences; Processes; Innovation; ACCNPQ::Ciências Sociais Aplicadas::Administração